(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Photonic Metamaterials are having wavelengths smaller than the wavelength of light and have diversified applications in sensing and imaging.The bibliometric analysis had been conducted to understand the active authors, organizations, journals, and countries involved in the research domain of “Photonic Metamaterial”.All published articles related to “Photonic Metamaterial” from “Scopus”, were analyzed using the VOS viewer to develop analysis tables and visualization maps.This article had set the objective to consolidate the scientific literature regarding the “Photonic Metamaterial”and also to find out the trends related to the same.The most active journals in this research domain were Optic Express and Science. The most active countries were China, Germany, and the United States of America. The leading organizations were the Tongji University of China and Karlsruhe Institute of Technology of Germany.The most active authors related to photonicMetamaterials were Linden S., Bade K. and Saile V.